A CONVERGENCE IN A RELIGION COMMODIFICATION AND AN EXPRESSION OF PIETY IN HALAL CERTIFICATION - Lisda Aisyah; Zulfa Makiah; Noorhaidi Hasan; Ali Sodiqin (UIN Antasari Banjarmasin, 2022)
The relationship among globalization, modernity, the escalation of religiosity in Southeast Asia, and capitalism cause halal trend consumption raising. The phenomenon of halal certification in Indonesia is interpreted by scholars in myriads of thoughts. Some scholars describe it as a form of religion commodification with more profit oriented, rather than referring to Islamic values or the philosophy of the halal concept. The Islamic symbols are used as trading commodities or marketing goods. The other scholars interpret the issue as an effort to manifest the religious teaching and an expression of piety. Halal certification is a diffusivity phenomenon of sacred (concept of halal, piety) with profane thing (trade and commodification). The existence of halal certification in Indonesia is urgent owing to the inability to control the escalation of products distribution in the domestic market as a result of the food technology, technological engineering, biotechnology and biological chemical processes developments. Moreover, the condition of Muslim in Indonesia and one of the expression of piety is by consuming halal products. Anthropological studies indicate that the character of religious people is always destined to seek and ensure that what is consumed does not hinder their intimacy with God because purity and impurity is important for religious people regarding to the supernatural presence. In fact, there is a contiguity between commodification and an expression of piety in halal certification. It could be interpreted simultaneously to find the convergence. The importance of supervising the halal certification validation agency and the creation of legal verdict must be proceed.